(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes issues related to the judge’s conscience in the administration of justice. Most importantly, it emphasizes the scientific aspects of problems associated with aligning criminal procedure legislation with moral and ethical norms. This article examines both national and foreign legislation, as well as the opinions of scholars.